1 - Une Nouvelle Expérience d’Intégration Régionale en Afrique: La Zone d’Echanges Préférentiels (ZEP) des Etats de l’Afrique de l’Est et de l’Afrique Australe: by Guy Martin - Guy Martin (Africa Development, 1989)
Operational since July 1984, the Presidential Trade Area (PTA) for Eastern and Southern Africa is a sub-regional grouping of fifteen states with the aim of creating an econo- mic community through the progressive removal of tariff and non-tariff barriers, facilitation of payments and setting up of common projects. In view of its short existence and compared to other African sub-regional groupings, PTA has had an impressive achievement A number of problem-areas such as definitions of rules of origin, assessment of economic costs and benefits and delays in or non-implementation of important community decisions need to be addressed. The ultimate goal of this promising new regional grouping will, to a large extent, depend on the concessions that the larger and more developed member states notably Kenya and Zimbabwe will be able to make in order to satisfy the demands of the rather reluctant and plainly frustrated smaller, underdeveloped member states particularly Burundi, Comoros, Djibouti and Rwanda.